PENGUATAN MODERASI BERAGAMA BAGI DA'I DAN KHATIB DI KOTA BANDAR LAMPUNG TAHUN 2023 - Amirudin; Fauzan, Ahmad; Muhammad, Nurwahidin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Based on statistical data, the population of Bandar Lampung city in 2021 reached 1,184,949 people, consisting of 603,532 males and 581,417 females. Furthermore, the religious composition in Bandar Lampung city based on Disdukcapil statistical data as of December 2021 shows that 93.4% of residents are Muslim, 3.4% Christian, 1.6% Catholic, 1.3% Buddhist, and 0.3% Hindu. Recently, the peaceful and serene city of Bandar Lampung was shocked by the arrest of Khilafatul Muslimin leader Abdul Qadir Hasan Baraja on Tuesday morning, June 7, 2022, at his center on WR. Supratman Street, Bumiwaras, Teluk Betung, Bandar Lampung. As reported, in mid-2022, followers of Khilafatul Muslimin in Bandar Lampung reached 2,000 people. A recent incident, as circulated on YouTube and other social media platforms, occurred in Rajabasa sub-district regarding a controversy over the use of a residential house for Christian worship activities, which culminated in the arrest of the local RT (neighborhood association) chairman, who was allegedly involved in prohibiting the use of the house for worship. This arrest by the Lampung Regional Police sparked solidarity among communities and mass organizations to demonstrate for the RT chairman's release. Efforts to voice the RT chairman's release by several Islamic mass organizations in Bandar Lampung were conducted peacefully at the Lampung High Prosecutor's Office. Meanwhile, the Bandar Lampung City Government, the Ministry of Religious Affairs Office, FKUB (Religious Harmony Forum), NU PVC Bandar Lampung, and MUI (Indonesian Ulema Council) coordinated to formally mediate regarding the detention, hoping to prevent the situation from escalating further. Based on these facts, the researchers, together with relevant parties, provide solutions and best alternatives to prevent further disintegration within the community and strengthen understanding of moderate and tolerant religious values through religious moderation strengthening activities for preachers and khatib (Friday sermon deliverers) in Bandar Lampung city. This activity was implemented by providing concepts of religious moderation and tolerance, delivering materials on religious moderation, practicing sermon text preparation, and practicing sermons based on religious moderation.